Share
Explore BrainMass

Gaussian Elimination and Back Substitution

X + 2y + z = 0
-3x + 3y + 2z = -7
4x - 2y - 3z = 2

Solution Preview

The system is
x+2y+z=0 (1)
-3x+3y+2z=-7 (2)
4x-2y-3z=2 (3)
By the Gaussian Elimination, we have the followings.

Step1: (2)+3*(1) and we get
x+2y+z=0 ...

Solution Summary

Gaussian Elimination and Back Substitution are described. The solution is detailed and well presented. The response received a rating of "5" from the student who originally posted the question.

$2.19